Gerakan Menuju Masyarakat Sipil: Membaca Gerakan Bantuan Hukum LBH - Suparman Marzuki (Fakultas Hukum Universitas Islam Indonesia, 2001)
Movement oflaw assistance is very possible tobeprohegemony ofstatesociatal move ment onadvocation setting ofhandelling cases in which thesociety faced bystate. Itis often that The Legal Aid Institute face a diliema in handelling the cases. On other side, there isinclination to raise a negotiation orlobbiying to statewith the risk ofreducing thesubtantive problem towards formal law problem andeven isolation ofsociety from sub stantive problem itself. On the otherside, thewayofadvocation is unvoidable from the formal law traps with the various kinds ofprocedures ofspecial mechanism. Although the movement of TheLegalAids Institute has not been an altemative socialmovement for cn'tical consciousness action for society through building contra-hegemonic, but is done historically, The Legal Aids Institute movement is still as organized movement in building the societal change.